Emulsions vs excipient emulsions as -tocopherol delivery systems: Formulation optimization and behaviour under in vitro digestion - Fernandes, J. M. (2024)
Oil-in-water emulsions (EM) have been extensively used for the encapsulation of lipophilic bioactive compounds and posterior incorporation into food matrices to obtain functional foods. Conversely, novel excipient oil-in-water emulsions (EXC) present identical composition and structure as EM, albeit are not bioactive by themselves since no bioactive compound is encapsulated. Instead, EXC aims at improving the bioavailability of foods natural bioactive compounds upon co-ingestion with nutrient-rich foods. In this work, EM and EXC were produced and their stability and functionality as delivery systems for -tocopherol compared. Emulsions were formulated with corn oil and lecithin, and their composition was optimized using experimental designs. Formulations produced with 3 % lecithin and 5 % oil attained smallest particles sizes with the lowest polydispersity index of all tested formulations and remained stable up to 60 days. Encapsulation of -tocopherol did not have a significative impact on the structural properties of the particles produced with the same composition. -tocopherol stability during in vitro digestion was superior in EM regardless the processing methodology (EM stability < 50 %, EXC stability < 29 %), indicating that EM offered greater protection against the digestive environment. -tocopherols bioaccessibility was significantly increased when encapsulated or when digested with added excipient emulsions (8292 % and 8790 % for EM and EXC, respectively). In conclusion, EM were more efficient vehicles for the selected bioactive compound, however, the good results obtained with EXC imply that excipient emulsions have a great potential for applications on foods to improve their natural bioactive compounds bioavailability without the need of further processing.